Program Peningkatan Keterampilan Literasi Pada Sekolah Unggul Di SD Muhammadiyah 9 Kota Malang - Maulana Hudan Daromi; Mohammad Syaifuddin (Jurnal Kebijakan dan Pengembangan Pendidikan, 2018)
Abstract: The Studi aims to describe 1) the strategy of improving literacy skills in superior schools in elementary school of Muhammadiyah 9 Malang. 2) the constraints of the strategy to improve literacy skills in superior schools in elementary school of Muhammadiyah 9 Malang. 3) the solution to the problem of improving literacy skills in superior schools in the elementary school of Muhammadiyah 9 Malang. The research method used is a qualitative approach with the type of research is descriptive. Data obtained through interviews, observation, and study documentation. Data analysis using Miles and Huberman analysis. After analyzing the data, the validity of the data is tested using triangulation techniques and extensions of observation. The results of the study show that literacy activities began in 2015. There was an increase in literacy skills at SD Muhammadiyah 9 Malang. Students who were originally only accustomed to reading non-text books, now students can already produce literacy products, namely books. The strategy to improve literacy skills at SD Muhammadiyah 9 Malang city refers to the three stages of school literacy. Starting from the habituation stage, development, until the implementation stage of literacy-based learning. The constraints of strategy in improving literacy skills in SD Muhammadiyah 9 Malang, include: (1) procurement of non-text reading books, (2) teacher literacy competencies are still low, (3) students' enthusiasm in literacy is low, (4 ) lack of funding, (5) narrow library space, (6) the absence of special staff as librarians. Solutions from strategic obstacles in improving literacy skills in SD Muhammadiyah 9 Malang, among others: (1) there are tuition fees for homeroom teachers and student guardians, (2) homeroom teachers make budget proposals, (3) schools work together with the literacy community, (4) socialization of funding to student guardians, (5) structuring library space, (6) assignments and scheduling teachers as a librarian.Keywords: Program, Improvement, Skills, Literacy Abstrak: Tujuan Penelitian yaitu untuk mendeskripsikan 1) strategi program peningkatan ketrampilan literasi pada sekolah unggul di SD Muhammadiyah 9 Kota Malang. 2) kendala strategi peningkatan keterampilan literasi pada sekolah unggul di SD Muhammadiyah 9 Kota Malang. 3) solusi permasalahan strategi peningkatan keterampilan literasi pada sekolah unggul di SD Muhammadiyah 9 Kota Malang. Metode penelitian yang dilakukan adalah pendekatan kualitatif dengan jenis penelitian adalah deskriptif. Data diperoleh melalui wawancara, observasi, dan studi dokumentasi. Analisis data menggunakan analisis Miles dan Hubberman. Setelah dianalisis maka data diuji keabsahannya dengan menggunakan teknik triangulasi dan perpanjangan pengamatan. Hasil penelitian menunjukkan bahwa 1) Pelaksanaan kegiatan literasi dimulai tahun 2015. Ada peningkatan keterampilan  literasi di SD Muhammadiyah 9 kota Malang. Siswa yang semula hanya terbiasa membaca buku non teks, sekarang siswa sudah bisa menghasilkan produk literasi yaitu buku. Strategi peningkatan keterampilan literasi di SD Muhammadiyah 9 kota Malang mengacu pada tiga tahapan literasi sekolah. Mulai dari tahap pembiasaan, pengembangan, sampai tahap penerapan pembelajaran berbasis literasi. 2) Kendala strategi dalam peningkatan keterampilan literasi di SD Muhammadiyah 9 kota Malang, antara lain: (1) pengadaan buku bacaan non teks, (2) kompetensi literasi guru masih rendah, (3) semangat siswa dalam literasi rendah, (4) kurangnya pendanaan, (5) ruang perpustakaan yang sempit, (6) tidak adanya tenaga khusus sebagai pustakawan. 3) Solusi dari kendala strategi dalam peningkatan keterampilan literasi di SD Muhammadiyah 9 kota Malang, antara lain: (1) adanya iuran wali kelas dan wali murid, (2) wali kelas membuat usulan anggaran, (3) sekolah bekerjasama dengan komunitas literasi, (4) sosialiasi pendanaan kepada wali murid, (5) penataan ruang perpustakkan, (6) penugasan dan penjadwalan guru sebagai pustakawan.Kata kunci: Program, Peningkatan, Ketrampilan, Literasi